2016
DOI: 10.1016/j.nedt.2015.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of virtual classroom training in improving the knowledge and key maternal neonatal health skills of general nurse midwifery students in Bihar, India: A pre- and post-intervention study

Abstract: Virtual classroom training was found to be effective in improving knowledge and key MNH skills of GNM students in Bihar, India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0
14

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 6 publications
4
45
0
14
Order By: Relevance
“…MMAT scores varied from 50% to 100% with five studies assessed at 100% (Holland, Smith, McCrossan, Adamson, Watt, & Penny, 2013;Ilott, Bennett, Gerrish, Pownall, Jones, & Garth, 2014;Kelly, Lyng, McGrath, & Cannon, 2009;Rigby, et al, 2012;Terry, Moloney, Bowtell, & Terry, 2016); two at 75% (Agrawal, Kumar, Balasubramaniam, Bhargava, Sinha, Bakshi et al, 2016;Lehmann, Thiessen, Frick, Bosse, Nikendei, Hoffmann et al, 2015), one at 60% (Sowan & Idhail, 2014) and two at 50% quality rating (Park, et al, 2016;Wang, Liang, Blazeck, & Greene, 2015).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…MMAT scores varied from 50% to 100% with five studies assessed at 100% (Holland, Smith, McCrossan, Adamson, Watt, & Penny, 2013;Ilott, Bennett, Gerrish, Pownall, Jones, & Garth, 2014;Kelly, Lyng, McGrath, & Cannon, 2009;Rigby, et al, 2012;Terry, Moloney, Bowtell, & Terry, 2016); two at 75% (Agrawal, Kumar, Balasubramaniam, Bhargava, Sinha, Bakshi et al, 2016;Lehmann, Thiessen, Frick, Bosse, Nikendei, Hoffmann et al, 2015), one at 60% (Sowan & Idhail, 2014) and two at 50% quality rating (Park, et al, 2016;Wang, Liang, Blazeck, & Greene, 2015).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…2 In-service training or so-called continuing health education will improve the quality of midwife by rendering more knowledge and competence. 3 Besides emphasizing antenatal care and birth preparedness practices through training, issues to optimal child growth and development in relation to healthy digestion, nutrition, and parenting are also substantial for midwife to manage child nutrition related conditions. 4,5 Furthermore child nutritional status is not merely affected by food intake.…”
mentioning
confidence: 99%
“…There is a significant increase in the performance skills of the students of Public Nursing School of the Indian state of Bihar, with respect to health practices for mothers and new-borns. Agrawal, et al (2016) and Alves, Miranda, and Morais (2017) concluded that there is a positive remarkable relation between the e-system usability, in general, and student skill performance. According to Gedera (2014) and Das (2016), the usage of synchronized virtual classrooms using Adobe Connect allowed the use of multiple templates, generally impact the rate of student active participation in e-learning activities.…”
Section: Discussionmentioning
confidence: 99%